Incorporating gender-sensitive traits in breeding programs - Beebe, Stephen E. (International Center for Tropical Agriculture, 2015)
Presented by Steve Beebe, International Center for Tropical Agriculture (CIAT) at the Joint Pan African Grain Legumes and World Cowpea Conference